Analysis of Indonesia's Non-Oil and Gas Export Potential with Non- Traditional Countries - Toengkagie, Reysa Rachmat; Ekananda, Mahjus (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2024)
This study aims to test the hypothesis regarding the effect of HRM Practices, Positive Emotions, and Knowledge Management on Employee Engagement, as well as the effect of Employee Engagement on Talent Retention in the Oil and Gas industry in Indonesia. This study uses a causal relationship model with a cross-sectional data method. It involves employees from PT Donggi Senoro LNG (DSLNG), JGC Indonesia (JIND), JOB Pertamina Medco E&P Tomori Sulawesi (JOB Group), and other Oil and Gas companies. Data was collected through questionnaires distributed via WhatsApp and Instagram using a purposive sampling technique. Data testing was carried out with validity and reliability tests, and analyzed using Structural Equation Modeling (SEM) with the AMOS application. The results showed that HRM Practices had no positive effect on Employee Engagement. However, Positive Emotions and Knowledge Management have a positive effect on Employee Engagement. In addition, Employee Engagement has a positive effect on Talent Retention. Thus, it can be concluded that Positive Emotions and Knowledge Management play an important role in increasing Employee Engagement, which in turn increases Talent Retention in the Oil and Gas industry in Indonesia.